“Real work for good pay and a community to belong to”: Creating Alternative Workplaces for People with Mental Illness - Buhariwala, Pearl (My University, 2013)
In recent years, paid work has taken on greater meaning for people living with mental illness. Paid work offers the chance to earn a wage, as well as opportunities for improved self- esteem, greater community participation and can reduce the chances of re-hospitalization. Although employment can offer many rewards, access to mainstream employment for people with mental illness remains been difficult as they often face discrimination and a lack of workplace accommodation. One response to these challenges has been the creation of social enterprises as ‘alternative spaces’ of employment for people with mental illness. Social enterprises are organizations with an entrepreneurial orientation whose focus is building social capacity rather than profit maximization. However, relatively little is known about the kinds of organizations that exist for people with mental illness in Ontario. This thesis uses data from key- informant interviews with organizations across Ontario to document the types of social enterprises that exist. The analysis also critically examines the strategies used by organizations to create jobs that are both suitable for people with mental illness, but also conducive to the ongoing success of the social enterprise.
Keywords: metal illness; mental health; social economy; social enterprises; employment; Human Geography; Inequality and Stratification; Other Geography; Other Mental and Social Health; Psychiatric and Mental Health; Social Policy; Human Geography